Reason as a Nexus of Natural Law and Rhetoric - Maciejewski, Jeffrey J. (Journal of business ethics, 2005)
Although the pages of Journal of Business Ethics have hosted an ongoing dialogue on the ethics of rhetoric and persuasion, the debates have been unable to account for the underlying morality of the human propensity to engage in rhetorical discourse as a part of living in society. In this paper, I offer natural-law ethical theory as a moral paradigm in which to examine rhetoric. In this context, I assert that rhetoric services reason, which in turn services our dispositions or inclinations that are one ideological foundation of natural-law theory. As rhetoric affects the apprehension of these dispositions it subsumes a related morality in which rhetorical endeavors can be seen as “natural”. So endowed, I believe that this conception of rhetoric offers a number of philosophical and practical implications, one of which is a new way to assess the morality of commercial manifestations of rhetoric such as spin and the use of puffery in advertising.